Clinical relevance of pharmacogenomic information for improving prescribing practices in acutely admitted older medical patients - Louise Westberg Strejby Christensen; Anne Kirstine Boas; Emilie Clausen; Nicoline Elers Koch; Anne Byriel Walls; Lotte Stig Nørgaard; Michael Asger Andersen; Anissa Aharaz; Rikke Lundsgaard Nielsen; Olivia Bornæs; Juliette Tavenier; Baker Nawfal Jawad; et al. (British Journal of Clinical Pharmacology, 2026)
Aims Safe prescribing and effective medication review during acute hospitalization depends on accurate information about liver and kidney function because these organs are responsible for the elimination of most medications. While estimates for kidney function are widely used, comparable markers of hepatic drug‐metabolizing capacity are not routinely available. We evaluated the clinical relevance of pharmacogenomic (PGx) information for key pharmacogenes implicated in medication elimination in older adults presenting to the emergency department. Methods Fourteen pharmacogenes were analysed using the Personal Medicine Profile™ test. GeneYouIn PillCheck™ software performed genotype‐to‐phenotype translations, identified drug–gene interactions (DGIs) and generated a clinical decision report based on each patient's actual medication use. Results Among 125 acutely admitted older medical patients (median age 78.3 years; 10 medications; 7 chronic diseases), PGx testing identified 88 DGIs across 63 patients (50.4%). Of these, 46.5% were considered by clinical experts to be clinically relevant for the individual patient, affecting 33 patients (26.4%) in the total study population. Frequently implicated pharmacogenes included CYP2C19 (25.0%), SLCO1B1 (25.0%), CYP2D6 (20.5%), CYP2C9 (14.8%) and OPRM1 (6.8%), and frequently implicated medications included losartan (13.6%), pantoprazole (12.5%), simvastatin (12.5%), atorvastatin (11.4%) and metoprolol (11.4%). Conclusion With more than one‐quarter of acutely admitted older medical patients having one or more clinically relevant DGIs, these findings suggest that PGx information may have meaningful clinical utility for improving prescribing practices in acute care. However, interpretation in this population requires careful consideration of other factors such as nutritional status and inflammation that may modify pharmacogene activity.